Jokowi in Political Contestation Towards 2024 Presidential Election - Ridha, Arif; Musliamin, Musliamin; Asry, Nahdatunnisa (Palakka : Media and Islamic Communication, 2023)
This research aims to analyze the political attitudes and strategies of Joko Widodo (Jokowi) in political contestation towards the 2024 Presidential Election through a semiotic approach to communication. This research examines further what the caricature of Koran Tempo version of Sokongan Bapak dan Partai Tetangga means. How the leadership and policies implemented by Jokowi affect the image and support of people who are backgrounded as active presidents. This research method uses the semiotic meaning analysis of Charles Sanders Pierce. The basis of this research is the political phenomena facing Jokowi, including the dynamics of political party competition, controversial issues, and public expectations of future leadership. The analysis also explores the potential global and regional impacts on domestic politics, as well as the role of social media in shaping public opinion related to Jokowi. The research is expected to contribute to a further understanding of political dynamics in Indonesia ahead of the 2024 Presidential Election, as well as providing an in-depth view of the political strategy that can be implemented by Jokowi to gain community support and face increasingly tight political competition.